PENERAPAN PERLINDUNGAN HUKUM KETENAGAKERJAAN TERHADAP PEKERJA WANITA PADA MALAM HARI DI PT EMBEE PLUMBON TEKSTIL - Asep Sholeh Fakhrul Insan; Syamsudin; E Sugianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The role of law in life is as a container of protection that provides a sense of security, peace and order to achieve peace and justice for everyone. One form of protection for national builders is the existence of regulations governing employment. The purpose of labor protection is to ensure the continuity of a harmonious labor relations system without any pressure from the strong to the weak. Women labor is part of the workforce that performs a job, either for themselves or working in an employment relationship or under orders either from employers or other legal entities. Development of employment needs to be directed to the creation of harmony between employers and workers imbued with Pancasila and the 1945 Constitution, where the parties respect and respect each other and understand each other's rights and obligations in the sustainability of the production process and participation in human resource development. The results of this study conclude that the protection of women's labor according to Law Number 13 of 2003 already covers the main matters regarding the rights that must be given to women, especially in the reproductive sector. Law Number 11 of 2020 concerning Job Creation has so far not harmed women's rights specifically. The implementation of protection of women workers at PT Embee Plumbon Tekstil, which includes: first, Equal employee benefits. Secondly, the issue of payment of wages. Third, menstrual leave. Fourth, maternity leave. Fifth, protection of child labor. Sixth, work time and rest hours. Seventh, occupational health and safety (K3).